2014
DOI: 10.1016/j.joca.2014.05.021
|View full text |Cite
|
Sign up to set email alerts
|

Human osteoarthritic synovium impacts chondrogenic differentiation of mesenchymal stem cells via macrophage polarisation state

Abstract: MSC chondrogenesis is inhibited by OA synovium CM through factors secreted by synovial macrophages and our findings suggest that M1 polarised subsets are potential mediators of this anti-chondrogenic effect. Modulation of macrophage phenotype may serve as a beneficial strategy to maximise the potential of MSCs for efficient cartilage repair.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
220
2
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 211 publications
(233 citation statements)
references
References 48 publications
10
220
2
1
Order By: Relevance
“…5A), in line with the presence of mixed M1/M2 phenotypes in the synovium of OA patients. 71 In particular, the proinflammatory marker IL-1b and wound healing markers Arginase-1 and VEGF-A mRNA were all significantly elevated in cocultured AMs regardless of chondrocyte disease state (i.e., cocultured with NCs or OACs). Interestingly, however, protein level analyses suggested that only OACs resulted in actual shifts in macrophage activation (Fig.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…5A), in line with the presence of mixed M1/M2 phenotypes in the synovium of OA patients. 71 In particular, the proinflammatory marker IL-1b and wound healing markers Arginase-1 and VEGF-A mRNA were all significantly elevated in cocultured AMs regardless of chondrocyte disease state (i.e., cocultured with NCs or OACs). Interestingly, however, protein level analyses suggested that only OACs resulted in actual shifts in macrophage activation (Fig.…”
Section: Discussionmentioning
confidence: 89%
“…These results suggest the emergence of mixed M1/M2 phenotypes at both the transcriptional and protein levels in AMs exposed to OACs, which is consistent with previously reported mixed macrophage subsets isolated from the synovium of OA patients. 71 …”
Section: System To Study Effects Of Osteoarthritic Inflammationmentioning
confidence: 99%
“…Macrophage depletion also resulted in decreased production of IL-6, IL-8, MMP-1, and MMP-3 (81). These findings suggest that activation of synovial macrophage is required for the production of MMPs leading to cartilage damage (82)(83)(84)(85). Natural killer cells have also been obtained from synovial tissues of patients undergoing total joint replacements, but the mechanism of pathogenesis has not yet been elucidated in detail (86).…”
Section: Correlation Between Synovitis and Oamentioning
confidence: 99%
“…7 Progression of OA occurs in conjunction with an increase in pro-inflammatory (M1) macrophages which not only exacerbate articular damage, but also reduce the chondrogenic potential of implanted MSCs. 4, 8 …”
Section: Introductionmentioning
confidence: 99%